(3GdEfJNGH aj cTa GdfbGH hYdhe GdMOjKs - (3CHh HQhSs
(3ChdgG (B:s
(3CeG HYO agPg CQLhRI ajef Qhi dg GdTjNGf ef GdGUMGH eNJUQ ef cTa GdfbGH ddMGaX UdGM GdOjf GdYdGFi dcfgG eQJHI Ydi CQHYI GHhGH s
(3BNQgG (B:s
(3jG QH aGQMe ef dgG bO fXeG aPfHg ef GdeYGUi YXekG dcfeG EYJeGOg MbkG Ydi Yah GdcQje aGJb GdSHY GdZdG Ke Ydi TaGYI GdeNJGQ eMeO eMeO MQ GdfGQ s
(3GdfSNI HgG MhGTs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdMOjK h GdeUWdMs